Expression, Purification and Characterization of Functional Teduglutide Using GST Fusion System in Prokaryotic Cells - Ali Akbar Alizadeh; Saba Rasouli; Omid Jamshidi Kandjani; Salar Hemmati; Siavoush Dastmalchi (Tabriz University of Medical Sciences, 2023)
Purpose: Teduglutide is the first and only FDA-approved drug for long-term treatment of short bowel syndrome (SBS). The current study aimed to present an approach for production of teduglutide using recombinant DNA technology. Methods: The coding gene for teduglutide was cloned into pGEX-2T vector, where coding sequence for factor Xa cleavage site was added between GST and teduglutide coding genes. The GST-teduglutide protein was overexpressed in E. coli BL21 (DE3) strain and affinity purified using glutathione sepharose affinity column. Results: On-column proteolytic activity of factor Xa followed by size exclusion chromatography resulted in the pure teduglutide. Circular dichroism (CD) spectropolarimetry showed that the produced teduglutide folds into mainly α-helical structure (>50%), as expected. In mass spectroscopy analysis, the fragments of teduglutide resulted by cyanogen bromide cleavage as well as those expected theoretically due to mass fragmentation were identified. The functionality of the produced peptide was evaluated by measuring its proliferative effect on Caco2 intestinal epithelial cells, and the results indicated that produced teduglutide induces cell proliferation by 19±0.30 and 33±7.82 % at 1.21 and 3.64 µM concentrations, respectively, compared to untreated cells. Conclusion: Teduglutide was successfully expressed and purified and its functionality and structural integrity were confirmed by in vitro experiments. We believe that the experimental-scale method presented in the current study can be useful for pilot-scale and also industrial-scale production of teduglutide.